Innovation and Development of HEIs. Competency Framework and Core Values of DUG’s Management Team - Gabriela Marchis (EIRP Proceedings, 2018)
The European integration and globalisation are two important challenges faced by the universities, together with the ageing process that affects the size and the distribution of the target group of any higher education institution – the students. In this context, the universities’ management system of human resources becomes very important. The performance and risks of any university are influenced by the quality of their employees and moreover, by the quality of the top-management team. This paper is trying to build on the model of recruitment developed by the Council of Europe, because HEIs need talented professionals, capable to work in multi-cultural environment. Thus, our paper tries to adapt the “Competency Framework and Core Values” of the Council of Europe to the specific of Danubius University of Galati, in order to improve the policy of recruitment, development and assessment of the management team. We hope that this paper will represent a starting point of redesigning the human-resources management system at our university, and also, it may represent an example of other universities in their process of renewing their strategies and policies of development. The value of this paper consists mainly in the innovative approach and to the fact that the results are original and unique and may be used for an education reform regarding HEIs’ management system.